THE ROLE OF SHARIA FINANCING ON SECTORAL GDP IN CENTRAL SULAWESI: MACROECONOMIC ANALYSIS WITH THE VAR/VECM APPROACH - Rita Yunus; Farida Millias Tuty; Ahmad Syatir; Novita Sari; Muhammad Akbar (JURNAL PROFIT, 2025)
Islamic financing in Indonesia is experiencing rapid growth and has the potential to become a key instrument in encouraging regional economic growth based on inclusive and sustainable principles. However, its effect on sectoral performance at the provincial level has not been studied empirically using a dynamic approach. This study aims to analyze the role of sharia financing and gross fixed capital formation (PMTB) on sectoral Gross Regional Domestic Product (GDP) in Central Sulawesi, covering the primary, secondary, and tertiary sectors. The analysis was conducted using quarterly data for the period 2022–2024 with the Vector Error Correction Model (VECM) approach for sectors showing long-term relationships and Vector Autoregression (VAR) for sectors without cointegration. Tests of stationarity, optimal lag, and Johansen cointegration were used to ensure the validity of the model. The results show that there is a difference in influence between sectors. In the primary sector, PMTB has a negative effect in the long term but positively in the short term. In the secondary sector, PMTB has a significant positive effect on both time horizons. In the tertiary sector, sharia financing has a significant positive effect in the short term without long-term relationships. This research offers novelty as the first post-pandemic sectoral study with a province-level dynamic model, which affirms the strategic role of Islamic finance in regional economic transformation. The implications of the research results show the need for sharia financing policies that are adjusted to sectoral characteristics to encourage inclusive, productive, and harmonized regional economic growth in line with Islamic economic principles.